The Two-Envelope Paradox Resolved. - McGrew, Timothy J.; Shier, David; Silverstein, Harry S. (Analysis, 1997)
Argues on the nature of two-envelope paradox. Consideration of prior probability distribution; Premise of equal probability; Formation of infinite set.